2020
DOI: 10.1021/acs.nanolett.0c01217
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Engineering in an Ultrasubwavelength Quantum System

Abstract: Many photonic and plasmonic structures have been proposed to achieve ultrasubwavelength light confinement across the electromagnetic spectrum. Notwithstanding this effort, however, the efficient funneling of external radiation into nanoscale volumes remains problematic. Here, we demonstrate a photonic concept that fulfills the seemingly incompatible requirements for both strong electromagnetic confinement and impedance matching to free space. Our architecture consists of antenna-coupled meta-atom resonators th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 36 publications
(63 reference statements)
1
29
0
Order By: Relevance
“…As in Ref. [2] we found that the radiation loss LC of the LC structures are negligeable, and they have non-radiative linewidth of LC=0.4 THz. By studying uncoupled LC resonators alone, we found that the annealing of the ohmic contacts introduces a frequency shift fLC=+0.56 THz that is taken into account in the final modelling shown in Figure 2.…”
Section: Reflectivity Curvessupporting
confidence: 79%
See 3 more Smart Citations
“…As in Ref. [2] we found that the radiation loss LC of the LC structures are negligeable, and they have non-radiative linewidth of LC=0.4 THz. By studying uncoupled LC resonators alone, we found that the annealing of the ohmic contacts introduces a frequency shift fLC=+0.56 THz that is taken into account in the final modelling shown in Figure 2.…”
Section: Reflectivity Curvessupporting
confidence: 79%
“…The fabrication procedure closely resembles the one described in Refs. [1,2], but has been adapted to improve the optical quality of the sample while coping with the high temperature annealings necessary to obtain ohmic contacts between the active region and the metallic parts.…”
Section: Sample Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…1(a). In the case of the ISB system, the radiative coupling of the ISB transition to free-space radiation is negligible [31,32]. The coupled system's response to an external excitation is given by…”
mentioning
confidence: 99%